Functional markers to predict forest ecosystem properties along a rural‐to‐urban gradient. (23rd March 2020) - Cardou, Françoise; Aubin, Isabelle; Bergeron, Alexandre; Shipley, Bill
Abstract: Questions: With increasing focus on urban sustainability, new tools are needed to manage urban woodlands for resilience and ecosystem service provision. Functional traits can provide quantitative and testable links between urban plant communities and specific ecosystem properties (functional markers). We ask whether commonly described multivariate patterns of trait association with urbanization (trait syndromes) capture changes in ecosystem properties associated with urbanization. Given that environmental heterogeneity can generate weak or non‐linear trait–ecosystem property relationships, we ask whether linear methods can yield functional markers with significant power for different ecosystem properties. Location: Montreal metropolitan area (Canada). Methods: We documented the functional composition of 43 woodlands along an urbanization gradient and measured proxies of three ecosystem properties: plant colonization, soil water infiltration and organic matter decomposition. We use redundancy analysis to identify traits associated with urbanization, and multiple linear regression and model selection to identify response and effect traits that best predict actual differences in ecosystem properties. We compare the resulting linear model with a non‐linear equivalent. Results: Traits associated with urbanization (urban syndrome) were inconsistently selected as best predictors of ecosystems properties (functional markers). Although predictive power varied between ecosystem properties, all three could be significantly predicted from community‐weighted traits (functional markers), with both response and effect traits contributing to the final model. When we fitted equivalent non‐linear models, we found that traits had largely non‐linear relationships with ecosystem properties. Conclusions: Our results demonstrate that community‐weighted traits of urban woodlands can yield functional markers that capture ecosystem properties, but these are inconsistently identified by "trait syndrome" approaches. In linear combinations, such functional markers provide a testable and generalizable way to quantify ecosystem properties in urban woodlands. Capturing such properties is one important step toward management of woodlands for their continued ability to provide ecosystem services into the future. Abstract : We investigate functional markers for important ecosystem properties in urban woodlands. Traits associated with urbanization are inconsistently selected as predictors of actual changes in colonization, soil water infiltration and plant litter decomposition. Linear functional markers only approximate true traitecosystem property relationships but capture significant portions of the variability, providing testable and generalizable tools to quantify ecosystem properties in urban woodlands.